Chronic PFOA exposure in vitro causes acquisition of multiple tumor cell characteristics in rat liver cells. (June 2023) - Qu, Wei; Yan, Yitang; Gerrish, Kevin; Scappini, Erica; Tucker, Charles J.; Dixon, Darlene; Merrick, B. Alex
Abstract: Perfluorooctanoic acid (PFOA) is tumorigenic in rats and mice and potentially tumorigenic in humans. Here, we studied long-term PFOA exposure with an in vitro transformation model using the rat liver epithelial cell, TRL 1215. Cells were cultured in 10 μM (T10), 50 μM (T50) and 100 μM (T100) PFOA for 38 weeks and compared to passage-matched control cells. T100 cells showed morphological changes, loss of cell contact inhibition, formation of multinucleated giant and spindle-shaped cells. T10, T50, and T100 cells showed increased LC50 values 20%, 29% to 35% above control with acute PFOA treatment, indicating a resistance to PFOA toxicity. PFOA-treated cells showed increases in Matrix metalloproteinase-9 secretion, cell migration, and developed more and larger colonies in soft agar. Microarray data showed Myc pathway activation at T50 and T100, associating Myc upregulation with PFOA-induced morphological transformation. Western blot confirmed that PFOA produced significant increases in c-MYC protein expression in a time- and concentration-related manner. Tumor invasion indicators MMP-2 and MMP-9, cell cycle regulator cyclin D1, and oxidative stress protein GST were all significantly overexpressed in T100 cells. Taken together, chronic in vitro PFOA exposure produced multiple cell characteristics of malignant progression and differential gene expression changes suggestive of rat liver cell transformation. Highlights: PFOA-treated cells showed loss of cell contact inhibition, formation of multinucleated giant and spindle-shaped cells PFOA-treated cells increased in MMP-9 secretion, cell migration, and developed more colonies in soft agar PFOA-treated cells increased c- Myc expression at both transcriptional and translational levels This study establishes an in vitro model for the evaluation of PFOA carcinogenesis